(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pterygium is an abnormal growth of the conjunctiva on the cornea that can cause significant visual impairment and aesthetic discomfort [6]. Traditional surgical treatment methods, such as pterygiumectomy with graft fixation using sutures, are accompanied by a long healing process, pain, and the risk of relapse [2, 3, 4, 5, 8, 9, 10]. The use of bioglue as an alternative to suture methods can reduce these risks, accelerate rehabilitation, and improve surgical results [1, 7, 11]. This study aims to evaluate the effectiveness of bioglue in autoplasty after pterygiumectomy.